Influence of trainee involvement on procedural characteristics for linear endobronchial ultrasound. Issue 5 (21st July 2017) - Nguyen, Sébastien; Ferland, Nancy; Beaudoin, Stéphane; Martel, Simon; Simon, Mathieu; Laberge, Francis; Lampron, Noel; Fortin, Marc; Delage, Antoine
Abstract : Background: Linear endobronchial ultrasound (EBUS) is a safe and effective method for the diagnostic sampling of mediastinal lymph nodes. However, there is a learning curve associated with the procedure and operator experience influences diagnostic yield. We sought to determine if trainee involvement during EBUS influences procedural characteristics, complication rate, and diagnostic yield. Methods: We performed a retrospective analysis of 220 subjects who underwent an EBUS procedure at our center from December 2012 to June 2013. Procedures were performed by six different interventional pulmonologists with substantial experience with EBUS or by a trainee under their direct supervision. Procedural characteristics and complications were recorded. Diagnostic yield and specimen adequacy were compared between groups. Results: EBUS was performed in 220 patients with a trainee involved ( n  = 116) or by staff physician alone ( n  = 104). Patient characteristics, and the number and size of lymph node stations sampled were similar. EBUS duration was longer (16.0 vs. 13.7 minutes; P  = 0.002) and the total dose of lidocaine used was higher (322.3 vs. 304.2 mg; P  = 0.045) when a trainee was involved. The rate of adequate specimens sampled was comparable between the groups (92.0 vs. 92.0%; P  = 0.60). Diagnostic yield was lower when a trainee was involved in the EBUS procedure (52.6 vs. 68.3%; P  = 0.02). Conclusion: Trainee involvement significantly increased EBUS duration and the dose of local anesthesia used for the procedure. Diagnostic yield was lower when a trainee was involved. Factors accounting for this difference in yield, despite adequate samples being obtained, warrant further investigation.